The pattern of lymph node metastasis in peripheral pulmonary nodules patients and risk prediction models - Ke, Lei; Ma, Honghai; Zhang, Qingyi; Wang, Yiqing; Xia, Pinghui; Yu, Li; Lv, Wang; Hu, Jian (Frontiers in Surgery, 2022)
Background: For peripheral pulmonary nodules, the regularity of lymph node (LN) metastasis has not been studied. This study aimed to evaluate the metastasis pattern of intrapulmonary and relevant mediastinal lymph nodes in early-stage lung cancer, and further selected patients who were of low risk of LN metastasis as potential population to receive sub-lobectomy. Methods: This study prospectively included consecutive patients with peripheral clinical T1N0M0 disease who underwent complete resection with LN dissection or sampling from August 2014 to July 2015. The patients were followed up to 15, May 2021. Univariable or multivariable Logistic analysis was used to identify the risk factors. Models predicting LN metastasis risk were conducted. The area under the curve for the receiver operating characteristic curves was used to evaluate the diagnostic value. Disease-free survival and overall survival were compared between groups. Results: Finally, 201 patients were included in this study. For patients with negative tumor-bearing (TB) 13 and 14 station LNs, the positive rate of other lymph node stations was extremely low. Maximum CT value, pleural indentation and CEA level were risk factors for N1 station LNs metastasis. Besides, the factors above and lobulation sign were risk factors for skip metastasis beyond TB 13 and 14 station LNs. We constructed two scoring tables to predict N1 station metastasis and skip metastasis beyond TB 13 and 14 station. The AUC were 0.837 and 0.823, respectively. Based on the first table, 40.9% of patients suffered N1 station LNs metastasis and 27.3% had N2 disease in “high risk group” while the proportion was only 5.7% and 4.5% in “low risk group”. For patients with negative TB13 and TB14 station LNs, based on the latter table, 11.1% of patients had N1 stations LNs metastasis and 16.7% had pN2 disease in “high risk group” while only 2.3% patients in “low risk group” suffered this kind of metastasis. Conclusion: For peripheral pulmonary nodules patients, stations 13 and 14 LNs may be the sentinel nodes. For patients with low risk of N1 metastasis and skip metastasis, sub-lobar resection might be sufficient for those who were of negative TB 13 and 14 station LNs.